1990
DOI: 10.1002/j.1460-2075.1990.tb07605.x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of human annexin V, an anticoagulant protein that binds to calcium and membranes.

Abstract: Human annexin V (PP4), a member of the family of calcium, membrane binding proteins, has been crystallized in the presence of calcium and analysed by crystallography by multiple isomorphic replacement at 3 A and preliminarily refined at 2.5 A resolution. The molecule has dimensions of 64 x 40 x 30 A3 and is folded into four domains of similar structure. Each domain consists of five alpha‐helices wound into a right‐handed superhelix yielding a globular structure of approximately 18 A diameter. The domains have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
275
1
7

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(291 citation statements)
references
References 59 publications
5
275
1
7
Order By: Relevance
“…the residues directly preceding Gly206, is the only bond in the annexin I1 core which is susceptible to limited trypsin digestion, indicating that this region is exposed at the surface of the protein (Johnson and Weber, 1990). In addition, the corresponding region in each repeat of annexin V forms an interhelical loop as determined by X-ray crystallography (Huber et al, 1990a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…the residues directly preceding Gly206, is the only bond in the annexin I1 core which is susceptible to limited trypsin digestion, indicating that this region is exposed at the surface of the protein (Johnson and Weber, 1990). In addition, the corresponding region in each repeat of annexin V forms an interhelical loop as determined by X-ray crystallography (Huber et al, 1990a).…”
Section: Discussionmentioning
confidence: 99%
“…The recently determined crystal structure of one member of the annexin family, annexin V, revealed that the protein core forms a highly symmetric unit with densely packed CIhelices (Huber et al, 1990a). Each annexin repeat is composed of five a-helices (a-e) which are connected via short loops or turns (Huber et al, 1990a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite fundamental differences, these models share a common concept of two distinct interaction sites; a primary site for membrane binding and a secondary site for membrane aggregation. The primary membranebinding site, which has been defined by extensive structural and mutational studies, coincides with the calcium-binding sites located on the convex surface of annexin molecules (20)(21)(22)(23)(24)(25)(26)(27). Much less is known about the secondary interaction site, although it has been postulated to be on the opposite concave side of the annexin molecule that harbors the aminoterminal region (19,28,29).…”
mentioning
confidence: 99%